Angelin Preljocaj's Empty Moves (2014) and Transmodern Dance History. Issue 1 (2nd January 2017) - Farrugia-Kriel, Kathrina
ABSTRACT: In this article, I examine the choreographic practices associated with French choreographer Angelin Preljocaj and his work, Empty Moves (Parts I, II & III), a three-part work informed by artistic hybridity and alterity. Through choreographic examples from Empty Moves, I examine the nascent state of transmodernism in dance, an artistic condition that implies a web of complex connections and interactions among dance histories and choreographic practices. In rethinking postmodern dance histories in the wake of recent theories of transmodernism, I conclude by offering a new framework for a dance paradigm and a reconsideration of selected canons of dance histories.